Development of a new test for determination of tensile strength of concrete blocks - Haach, Vladimir G. (2013)
An accurate experimental, numerical and analytical analysis of masonry structures is only possible if detailed information on the mechanical properties of masonry materials is known. In general, tensile strength of fragile brittle materials is a property difficult to measure in direct tensile tests. In this paper a new indirect tensile test method is proposed for determination of tensile strength of concrete blocks based on compression tests of blocks in the direction parallel to bed joints. Results of the proposed test are compared with direct tensile tests of small specimens cut from the concrete blocks. The compression test seems to be an alternative method of measuring the tensile strength of the units since it is easier to carry out and avoids problems like rotation of the specimen and debonding of the specimens from the plates.